TopUp SERS substrates with integrated internal standard - Patze, Sophie; Huebner, Uwe; Weber, Karina; Cialla-May, Dana; Popp, Juergen (Materials, 2018)
Surface-enhanced Raman spectroscopy (SERS) is known as a molecular-specific and highly sensitive method. In order to enable the routine application of SERS, powerful SERS substrates are of great importance. Within this manuscript, a TopUp SERS substrate is introduced which is fabricated by a top-down process based on microstructuring as well as a bottom-up generation of silver nanostructures. The Raman signal of the support material acts as an internal standard in order to improve the quantification capabilities. The analyte molecule coverage of sulfamethoxazole on the surface of the nanostructures is characterized by the SERS signal evolution fitted by a Langmuir-Freundlich isotherm.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Langmuir-Freundlich isotherm; SERS; Sulfamethoxazole; TopUp SERS substrate